Musical Revolutions in German Culture - Hall, M. author. aut Link
XVI, 214 p.
Keywords: Drawing upon the philosophical insights of Friedrich Schlegel, Walter Benjamin, Theodor W. Adorno, and Blixa Bargeld, this book explores the persistence of a critical-deconstructive approach to musical production, consumption, and reception in the German cultural sphere of the last two centuries.